DOSE DISTRIBUTION ANALYSIS OF PROTON THERAPY FOR MEDULLOBLASTOMA CANCER WITH PHITS 3.24 - Moh. Miftakhul Dwi Fianto; Yohannes Sardjono; Andang Widi Harto; Isman Mulyadi Triatmoko; Gede Sutresna Wijaya; Yaser Kasesaz (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
One of the developments in particle therapy is proton radiation therapy. Meanwhile, a limited number of available proton therapy facilities makes research related to proton therapy difficult. Therefore, there is a need for alternative proton therapy simulations using programs other than those in proton therapy facilities. This research was aimed to simulate medulloblastoma brain cancer which children often experience.The program used in this research was PHITS version 3.24. The human body was modeled with the revised ORNL-MIRD phantom for a 10-year-old child. The therapy scheme was a whole posterior fossa boost of 19.8 Gy. The proton passive scattering was simulated by passing a uniform proton beam through the aperture and compensator with energy variations. The proton pencil beam scanning was simulated with small cylindrical beams with a radius of 0.5 cm, which were adjusted to the planning target volume with layers variations.The total duration to give the prescription dose was 550 seconds with passive scattering and 605 seconds with pencil beam scanning. In passive scattering, the OAR(s) with the most significant percentage of absorbed dose were the skin, cranium, and muscle, i.e., 8.22 ± 0.15 %, 5.51 ± 0.05 % and 1.39 ± 0,04 % respectively to their maximum tolerated dose, while in the pencil beam scanning, the OAR(s) with the most significant percentage of absorbed dose were the skin, cranium, and muscle, i.e., 5.42 ± 0.08 %, 4.43 ± 0.05 % and 0.51 ± 0.05 % respectively to their maximum tolerated dose. Dose distribution in passive scattering was relatively better than in pencil beam scanning in terms of dose homogeneity using dose sampling analysis at some points within the planning target volume.